Plasma membrane folding enables constant surface area-to-volume ratio in growing mammalian cells - Wu, Weida; Lam, Alice R; Suarez, Kayla; Smith, Grace N; Duquette, Sarah M; Yu, Jiaquan; Mankus, David; Bisher, Margaret; Lytton-Jean, Abigail; Manalis, Scott R; Miettinen, Teemu P (Current biology, 2025)
All cells are subject to geometric constraints, including the surface area-to-volume (SA/V) ratio, which can limit nutrient uptake, maximum cell size, and cell shape changes. Like the SA/V ratio of a sphere, it is generally assumed that the SA/V ratio of cells decreases as cell size increases. However, the structural complexity of the plasma membrane makes studies of the surface area challenging in cells that lack a cell wall. Here, we investigate near-spherical mammalian cells using single-cell measurements of cell mass and plasma membrane proteins and lipids, which allow us to examine the cell size scaling of cell surface components as a proxy for the SA/V ratio. Surprisingly, in various proliferating cell lines, cell surface components scale proportionally with cell size, indicating a nearly constant SA/V ratio as cells grow larger. This behavior is largely independent of the cell-cycle stage and is also observed in quiescent cells, including primary human monocytes. Moreover, the constant SA/V ratio persists when cell size increases excessively during polyploidization. This is enabled by increased plasma membrane folding in larger cells, as verified by electron microscopy. We also observe that specific cell surface proteins and cholesterol can deviate from the proportional size scaling. Overall, maintaining a constant SA/V ratio ensures sufficient plasma membrane area for critical functions such as cell division, nutrient uptake, growth, and deformation across a wide range of cell sizes.